Body over troubled waters [large type] - Swanson, Denise (Swanson, Denise. Welcome back to Scumble River, 2022)
"Love is deadly Stupid Cupid is making School psychologist Skye Denison-Boyd regret returning to work after her maternity leave. It starts with an emergency school lockdown, continues with her godfather's arrest by the state police, and ends with a dead body! It's every teacher and administrator's worst nightmare--a school shooter lockdown. And even worse for Skye because she's trapped in a tinyroom with the district's creepy superintendent, Dr. Wraige while they wait for the all-clear. When Dr. Wraige turns up dead in his home just a short time later, is it a coincidence, or something more? Skye joins her police chief husband, Wally, in an investigation that becomes more complicated by the minute. With a dead boss and a mysterious killer on the loose, Skye is caught between a rock and a heart place--but she won't give up until Scumble River issafe once again"--